Η αυτοπεποίθηση των μητέρων για τον μητρικό θηλασμό και οι απόψεις τους για την εφαρμογή των «δέκα βημάτων» στα μαιευτήρια της Λευκωσίας, κατά τις πρώτες 48 ώρες - Χατζηιωνά, Βασιλική (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
Introduction: Breastfeeding is recognized globally as the ideal way of feeding the newborn. The obstetrics departments are required to implement the practice of "ten steps" by WHO & UNICEF, and the adoption of the International Code of Marketing of Breast-Milk Substitutes , thereby helping to promote the successful establishment and continuation of breastfeeding . Aim: To evaluate the confidence and explore the views of mothers in the implementation of the "ten steps" to successful breastfeeding, during the first 48 hours after birth, in public and private maternity departments in Nicosia. Material and method: Descriptive correlational design was used. Study population consisted of 216 mothers, aged 18 or more, who gave birth to full-term healthy infants at Obstetric Clinics in Nicosia (one public and 7 private), from January to April 2014 (10 weeks). Tools: 1.The questionnaire of WHO & UNICEF, which is addressed to mothers leaving the maternity unit. 2.The BSES-SF questionnaire which measures the perceived maternal confidence in breastfeeding. Results: The level of confidence in mothers has averaged 3.33 ( 0.87 TA ) in the 1-5 Likert 5 -point scale. Offering assistance for breastfeeding skills development, is more implicated in maternity wards of Nicosia, along with the encouragement of breastfeeding on baby’s demands (steps 5th & 8th). Helping mothers about breastfeeding has a higher percentage of private maternity clinics (small & large 98.2 % 92.1%, Vs 87.9%). The information given about the importance of skin to skin contact between mother and baby, during antenatal period, is at a higher level in the public maternity hospital (51.5% Vs 25.7%), although in practice this is applied more efficiently in the private sector (29.0% Vs 25.4 %). The rate of exclusive breastfeeding appears higher in the public maternity hospital (33.3%) instead in private (23.9% large, 5.2% small clinics). Conclusions:. This study showed that the self-confidence of mothers is almost in the center of the scale (1-5). It was also found that mothers had limited experience from the application of the "ten steps". However, the International Code of Marketing of Breast-milk substitutes, is applied to a higher degree. The results of this study underline the need for further effort to the implementation of the "ten steps".
Keywords: Breastfeeding; International Code of Marketing of Breast-milk Substitutes; Newborn; Questionnaire; Μητρικός Θηλασμός; Διεθνές Κώδικας Εμπορίας Υποκατάστατων Μητρικού Γάλακτος; Νεογνό; Ερωτηματολόγιο; Έρευνα